1997
DOI: 10.1038/sj.ijo.0800407
|View full text |Cite
|
Sign up to set email alerts
|

Lipolytic catecholamine resistance linked to α2-adrenoceptor sensitivity—a metabolic predictor of weight loss in obese subjects

Abstract: OBJECTIVE: The weight loss achieved during treatment with very-low-calorie diets (VLCD) varies between individuals. The aim of this study was to investigate whether interindividual variations in catecholamine-induced lipolysis are of importance for the rate of weight loss during VLCD. DESIGN: Prospective study. SUBJECTS: Twenty-eight obese, but otherwise healthy and drug-free women aged 20±57 y with BMI 33.3±47.5 kg/m 2 were investigated before entering a four week weight reduction program with a calorie-restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 7 publications
1
17
0
1
Order By: Relevance
“…was more striking in untrained obese subjects with higher adipocyte volume than in untrained nonobese subjects, and Hellström et al have shown that, after weight loss during very low-calorie diet, ␣ 2 -AR sensitivity decreased (16). However, when obese subjects were trained for 3 mo, although their weight did not change, the antilipolytic effect of ␣ 2 -AR in vitro was decreased (6); this illustrates the effect of training on AR activity.…”
Section: Discussionmentioning
confidence: 96%
“…was more striking in untrained obese subjects with higher adipocyte volume than in untrained nonobese subjects, and Hellström et al have shown that, after weight loss during very low-calorie diet, ␣ 2 -AR sensitivity decreased (16). However, when obese subjects were trained for 3 mo, although their weight did not change, the antilipolytic effect of ␣ 2 -AR in vitro was decreased (6); this illustrates the effect of training on AR activity.…”
Section: Discussionmentioning
confidence: 96%
“…8,9 However, a reduced sensitivity to the lipolytic effect of catecholamines has been evidenced in young obese; 10 more importantly, the individual responsiveness to the catecholamine-induced lipolysis is predictive of the rate of body weight loss, during energy restriction. 11 From all these data, it clearly appears that the SNS is sensitive to both positive and negative energy balance. Moreover, an impaired capacity of the SNS to adapt to modifications of energy balance could either contribute to the development of obesity and/or hamper body weight loss.…”
Section: Introductionmentioning
confidence: 93%
“…www.e-jkmr.org 91 Hellström 28) also found that plasma NA and α 2 -adrenergic receptor sensitivity are associated with weight loss during 4 weeks on diet restriction. These three studies suggest that plasma NA can be used as a prognostic marker for treating obesity.…”
Section: Discussion»»»mentioning
confidence: 96%
“…These findings show that constitutional differences in ANS activity may explain the variability in weight loss observed by obese subjects 17) . Nevertheless, it is insufficient to show that the ANS can predict the propensity to lose weight in obese individuals, and all interventions in those studies [26][27][28] were dietary restriction.…”
Section: Discussion»»»mentioning
confidence: 99%